Acquistion of Culture and a Historical Approach to the Relationship between Art and Culture - Zeybek, Hasan (Journal of the University of Zulia, 2020)
Within the scope of the study, the awareness of human beings toward their existence and the ontological relations they have established with the place of their origin compels us to reconsider and study the connection between human beings to their society and environment within the general terminology of the bond of belonging. This includes the daily life practices, behaviour and habits that constitute the code of values which define our identity and culture. The perpective towards the history of civilization in this essay is defined as steeming from the liberation of the hand; the history of a species which liberated and obtained the ability to use their hand in nature together with the potential to transform the conditions of surrounding enviroment whilst living and grouping collectively under societies and other groups. The cornerstones of the history of civilization have been reevaluated by considering various works of art in line with the definition. The content of works of art are studied as the result of ‘artistic action’ in relation to society. The action being taken as culture and values of the artist who produced the work of art, the production and how the work was perceived are elements of it. The most profound idea that art works carry information and value reflecting sociological, social and cultural values provide the basis of the new perspective to the relationship between culture and art.